Pengaruh Hypnosis Terhadap Tingkat Kecemasan Ibu Hamil Nullipara Triwulan III Dalam Persiapan Menghadapi Persalinan - Sugeng Triyani; Fatimah Fatimah; Aisyah Aisyah (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2016)
Adaptability of pregnant women toward labor preparation is very important. If the mother cannot adapt during the process of labor, usually she will experience anxiety and will give a response of fight or flight triggered by the abundance of Catecholamines hormones and by the presence of fear and other forms of distress. This research used a quasi experiment method with non randomized pretest potest equivalent group design, without intervention on the comparison group. The quetionnaire of Hamilton Anxiety Rating Scale was used to measure the level of anxiety among pregnant women given hypnosis therapy with pregnant women not given the hypnosis therapy. The results showed that there was a significant difference in the mean level of anxiety between cases and controls (SD of 6,004). There was a significant influence on the group that used hypnosis therapy with a mean decrease in anxiety by 21.550 poin with a p value of < 0.001. Therefore, hypnosis is effective in reducing anxiety among nulliparous women in the third quarter of pregnancy.